A novel trypsin of Trichinella spiralis mediates larval invasion of gut epithelium via binding to PAR2 and activating ERK1/2 pathway. - Lu Lu Han; Qi Qi Lu; Wen Wen Zheng; Yang Li Li; Yan Yan Song; Xin Zhuo Zhang; Shao Rong Long; Ruo Dan Liu; Zhong Quan Wang; Jing Cui (Public Library of Science (PLoS), 2024)
Background Proteases secreted by Trichinella spiralis intestinal infective larvae (IIL) play an important role in larval invasion and pathogenesis. However, the mechanism through which proteases mediate larval invasion of intestinal epithelial cells (IECs) remains unclear. A novel T. spiralis trypsin (TsTryp) was identified in IIL excretory/secretory (ES) proteins. It was an early and highly expressed protease at IIL stage, and had the potential as an early diagnostic antigen. The aim of this study was to investigate the biological characteristics of this novel TsTryp, its role in larval invasion of gut epithelium, and the mechanisms involved. Methodology/principal finding TsTryp with C-terminal domain was cloned and expressed in Escherichia coli BL21 (DE3), and the rTsTryp had the enzymatic activity of natural trypsin, but it could not directly degrade gut tight junctions (TJs) proteins. qPCR and western blotting showed that TsTryp was highly expressed at the invasive IIL stage. Immunofluorescence assay (IFA), ELISA and Far Western blotting revealed that rTsTryp specifically bound to IECs, and confocal microscopy showed that the binding of rTsTryp with IECs was mainly localized in the cytomembrane. Co-immunoprecipitation (Co-IP) confirmed that rTsTryp bound to protease activated receptors 2 (PAR2) in Caco-2 cells. rTsTryp binding to PAR2 resulted in decreased expression levels of ZO-1 and occludin and increased paracellular permeability in Caco-2 monolayers by activating the extracellular regulated protein kinases 1/2 (ERK1/2) pathway. rTsTryp decreased TJs expression and increased epithelial permeability, which could be abrogated by the PAR2 antagonist AZ3451 and ERK1/2 inhibitor PD98059. rTsTryp facilitated larval invasion of IECs, and anti-rTsTryp antibodies inhibited invasion. Both inhibitors impeded larval invasion and alleviated intestinal inflammation in vitro and in vivo. Conclusions TsTryp binding to PAR2 activated the ERK1/2 pathway, decreased the expression of gut TJs proteins, disrupted epithelial integrity and barrier function, and consequently mediated larval invasion of the gut mucosa. Therefore, rTsTryp could be regarded as a potential vaccine target for blocking T. spiralis invasion and infection.